Posterior reversible encephalopathy syndrome with reversible cerebral vasoconstriction syndrome in a normal primigravida woman at the 35-week gestational stage: a case report - Shingo Tanaka; Maki Goto; Saya Watanabe; Sachino Kira; Sotaro Hayashi; Shigeki Fujimoto; Miho Oda; Lifa Lee; Yoko To; Satoshi Nishiyama; Fuyuki Eguchi; Hiroshi Tsujioka (Clinical and Experimental Obstetrics & Gynecology)
Background: Herein, we report a case of cerebral hemorrhage in a 21-year-old nulliparous, primi gravida woman caused by posterior reversible encephalopathy syndrome (PRES), which may be associated with reversible cerebral vasoconstriction syndrome (RCVS). Case: The patient’s medical history was unremarkable, apart from the mother having had a cerebral infarction. She had been examined by a local doctor, and showed good progress; however, her blood pressure (BP) was 143/97 mmHg, she had findings of proteinuria (3+) and she had a headache on the 35th week with multiple vomiting episodes. She was admitted to our hospital after poor responsiveness and a consciousness level of GCS14, E4V4M6, a BP of 143/97 mmHg, a pulse rate of 77/min, bilateral abduction of the eyes, and left hemiplegia. Cranial computed tomography (CT) revealed cerebral hemorrhage with ventricular puncture in the right caudate nucleus. Emergency caesarean section was performed on the same day with priority given to maternal lifesaving. Acute cerebral infarction findings and PRES were observed on head magnetic resonance imaging (MRI) on the admission day 1. Head MR angiography on the 4th hospital day showed narrowing of the entire main artery trunk, suspected as RCVS. Short-term memory deficits were diagnosed post-extubation, but gradually improved. Although it became possible and hematoma in the ventricles were absorbed, left paresis and higher dysfunction were observed, and she was discharged on the 21st hospital day. Conclusion: PRES and RCVS occur simultaneously quite frequently, but require opposing treatment approaches. Both cases are reversible, but if they occur simultaneously, RCVS, which progresses slowly, may cause irreversible symptoms, thereby requiring careful treatment.